PERSEPSI KEPALA SEKOLAH TERHADAP PENERAPAN PERATURAN DAERAH KOTA BANDAR LAMPUNG - Viki Septian; Berchah Pitoewas; Hermi Yanzi (FKIP Unila, 2015)
The focus of this study was to determine the perceptions of principals on the implementation of the Regional Regulations in the city of Bandar Lampung No. 01 year 2012 on the provision of education in relation to the number of the quota of incoming regular students and environmental development pathways that impact on the provision of education and the efficiency of learning in school. This research is quantitative research with the object of study is 17 principals in SMA N in Bandar Lampung. The data collection technique is the basic technique of the questionnaire and the data were analyzed using a percentage. Based on the research that has been done, it can be seen that the perception of the Principal of the Implementation of the Regional Regulation in Bandar Lampung City No. 01 year 2012 on the Implementation of Education does not agree with any of the content of the regulation related to entry quotas and non-environmental development paths for environmental development.Fokus penelitian ini untuk mengetahui persepsi kepala sekolah terhadap penerapan Peraturan Daerah Kota Bandar Lampung No. 01 Tahun 2012 tentang penyelenggaraan pendidikan dalam kaitannya dengan jumlah kuota masuk siswa jalur regular dan jalur bina lingkungan yang berdampak pada penyelenggaraan pendidikan dan efisiensi pembelajaran di sekolah. Jenis penelitian adalah penelitian deskriptif kuantitatif dengan objek penelitian adalah 17 kepala sekolah di SMA Negeri se-Kota Bandar Lampung. Teknik pengumpulan data teknik pokok angket dan analisis data menggunakan persentase. Berdasarkan hasil penelitian yang telah dilakukan dapat diketahui bahwa persepsi Kepala Sekolah terhadap Penerapan Peraturan Daerah Kota Bandar Lampung Nomor 01 Tahun 2012 tentang Penyelenggaraan Pendidikan tidak setuju dengan salah satu isi Peraturan tersebut yang berkaitan dengan kuota masuk jalur bina lingkungan dan non bina lingkungan.Kata kunci: kepala sekolah,penyelenggaraan pendidikan, peraturan daerah kota bandar lampung nomor 01 tahun 2012.